Dissenting Opinion dan Concurring Opinion dalam Putusan Mahkamah Konstitusi - Adam, Haidar (Al-Jinayah: Jurnal Hukum Pidana Islam, 2017)
Abstract: This article discusses about dissenting opinion and concurring opinion in the decision of the Constitutional Court. Law enforcement can be done through the Constitutional Court in the form of law judicial review. The issue of dissenting opinion is regulated through Law No. 24 Year 2003 and Constitutional Court Regulation No. 6 of PMK Year 2005 concerning Procedural Law of Tests of Act. The phrase used in the Constitutional Court Law is âthe different opinion of the judiciary members". The different opinion, according to Jimly, is divided into two namely dissenting opinion and concurrent opinion. A verdict is considered concurring if there is an argument by a member of the panel of judges that is different from that of the other members of the judiciary but it does not affect the difference of the decision. On the other hand, a decision is said to be dissenting if the opinion of a member of the panel of judges is different from that of the majority of the other members of the panel of judges and the difference is not merely in the case of reasoning but to touching on the verdict. Keywords: Dissenting opinion, concurring opinion, the court constitutionâs decision. Abstrak: Penegakan hukum dapat dilakukan melalui pengadilan oleh Mahkamah Konstitusi dalam bentuk pengujian terhadap undang-undang. Masalah dissenting opinion diatur melalui Undang-Undang Nomor 24 Tahun 2003 dan Peraturan Mahkamah Konstitusi Nomor 6 PMK Tahun 2005 tentang Hukum Acara Pengujian Undang Undang. Frase yang dipakai dalam UUMK adalah âpendapat anggota majelis hakim yang berbedaâ. Pendapat yang berbeda menurut Jimly, dibedakan menjadi dua yaitu dissenting opinion dan concurrent opinion. Suatu putusan dianggap sebagai concurring apabila terdapat argumentasi anggota majelis hakim yang berbeda dengan mayoritas anggota majelis hakim yang lain, namun tidak berimbas pada perbedaan amar putusan. Di sisi lain, suatu putusan dikatakan dissenting, jika pendapat suatu anggota majelis hakim berbeda dengan pendapat mayoritas anggota majelis hakim yang lain dan sampai menyentuh pada amar putusan. Kata Kunci: Dissenting opinion, concurring opinion, putusan Mahkamah Konstitusi.